Effect of pH on Adsorption of Cr(III) and Cr(VI) by zeolite A (from Fly Ash) Modified Surfactant HDTMA - Jumaeri Jumaeri; Juari Santosa; Sutarno Sutarno; Ella Kusumastuti (Indonesian Journal of Physics and Nuclear Applications, 2016)
Adsorption of Cr(III) and Cr(VI) in aqueous solution by the zeolite A from coal fly ash modified hexadecyltrimethylammonium bromide (HDTMAB) at various pH conditions has been carried out. Zeolite A was synthesized from fly ash through modified alkaline fusion hydrothermal process in a reactor stainless steel. The surface modification was performed using cationic surfactant HDTMAB twice as much as the cationic exchange capacity of the elite A resulted. The surfactant modified zeolite A was then applied to adsorption the metal ion chromium as Cr(III) and Cr(VI) in aqueous solution. The results showed that the  acidity (pH)  of adsorption conditions, affect the ability of adsorption surfactant modified zeolite A (SMZA) to Cr(III) and Cr(VI) in aqueous solution. The optimum pH conditions for the adsorption of Cr(III) and Cr(VI) on SMZA exist at pH 6. Surfactant modified zeolite A capable to adsorb either cation Cr(III) or anion Cr(VI).  Adsorption of SMZA on Cr(III) increased from 36.30% to 97.04% with the increase the acidity of pH of 2 to 6. Adsorption SMZA to Cr(VI) is lower than the adsorption of the Cr3+, adsorption increasing from 19.63 to 64.07% with increase pH of 2 to 6